Efektivitas Penyelenggaraan Konseling dengan Memahami Komunikasi antar Budaya - Iswari, Mega (Konselor, 2017)
Cross- cultural counseling is done in different cultures , given to minority groups that the counseling process is a cultural encounter between counselor and client it serves. Problematic behavior will be different in different cultures , as well as the adjustment. So that effective counseling process, counselors are required to have cultural sensitivity and break away from cultural biases, understand and can appreciate and have skills that are culturally responsive. Communication activities between nations is a consumption activity that occurs between different clients mores, race, language, religion, level of education, social status or even gender. Thus intercultural communication should be by the diplomacy of foreign astudents, a teacher at an international school , social workers and others.To be able to understand more , intercultural communication as well as some that affect communication (1) Comunication approach, (2) Communication barriers between cultures, (3) How can these barriers interfere with communication between cultures. At the time of counseling , the counselor does not deal with the client's culture but also cultural counselor with individual clients. This view is dangerous for the counseling process, as it would appear culturally insensitive counselor, unsympathetic and very likely impose its own cultural values to the clients it serves.